Research on the Problems and Countermeasures of Emergency Rule of Law - Liu, Xiaoli (Journal of Theory and Practice of Management Science, 2024)
In the post-epidemic era, as the world has entered a new era, there are both crises and development opportunities, in which the value of the rule of law has been reflected. As a specific manifestation of public health emergencies, the epidemic situation presents a special legal state after all countries enter the state of emergency. However, although the state of emergency has been improved at present, the disadvantages of the rule of law in emergency response are becoming more and more prominent. Therefore, by studying the main problems in the post-epidemic era of emergency rule of law, this paper puts forward several measures to solve them, so as to promote the perfection of the legal system of emergency state, develop the relationship with other values on the premise of safety, and promote the perfection of emergency rule of law.